MULTILEVEL SEBAGAI ANALISA PENDAPATAN USAHA MIKRO, KECIL DAN MENENGAH (UMKM) DI PROVINSI ACEH - Wanda Sri Noviana; Miftahuddin Miftahuddin; Eddy Gunawan (Universitas Negeri Gorontalo, 2021)
Studies the influence of the MSME sector and regional categorical factors is often overlooked, so in this case a simple regression can be improved through classifying similar data sets and being handled properly. Therefore, to increase understanding of the factors that affect the income of MSMEs, it must be considered by looking at the relationship between the categories of the MSME sector and different districts / cities (regions) especially in Aceh Province. One of the analysis models suitable for MSME data is multilevel regression analysis. The purpose of this multilevel regression analysis is to form a regression model on the amount of MSME income in Aceh Province where individual level 1 business owners with factors of type of business, number of workers and amount of capital, are nested in the level 2 MSME sector, nesting in level 3 districts / cities. The data used are UMKM data obtained from the Aceh Cooperative and UMKM Service. The data were processed and analysed using the R-Studio software. The results showed that the type of mining, agriculture and livestock businesses had a significant negative effect of 5% on the income of MSMEs in Aceh Province, while the types of transportation, capital and labor businesses had a significant positive effect of 5%. The measure of suitability of the 3-level regression model obtained deviance, AIC and BIC, respectively, is 22,571, 22,585 and 22,636.